RANCANG BANGUN SISTEM PERINGATAN DINI BAHAYA AKTIVITAS GUNUNG BERAPI BERBASIS MIKROKONTROLER ARDUINO - Michael Angelo Vincensio Simon; Widyadi Setiawan; Nyoman Putra Sastra (Program Studi Teknik Elektro UNUD, 2020)
This research aims to design and build an early warning system device of volcanoactivity hazards based on Arduino microcontroller that can monitor changes in temperature, soilmoisture and tremor through sensors placed in the environment around the crater. This earlywarning system of volcano activity hazards is relatively simple but can be very useful to helpgovernment institutions and also the public which will reduce the risk of data collection directlyand also speed up the public to get information so that they can avoid the radius of danger. Theearly warning system of volcano activity hazards is also flexible with wifi coverage areas thatrange more than 100 meters. Based on research and test that has been done shows that thesystem created has a good effectiveness and flexibility which is able to send monitoring resultsto the ThingSpeak and then display it on a smartphone application in realtime.